Experiments with two different approaches to gridding terrestrial gravity anomalies and their effect on regional geoid computation - Featherstone, Will; Goos, Joris; Kirby, Jon; Holmes, S. (Commonwealth Association for Surveying and Land Economy, 2003)
This paper compares the gridding of two types of terrestrial gravity anomaly prior to the computation of regional gravimetric geoid models over Australia. The aim is to investigate the effects of high-frequency components (by way of the terrain correction) on the resulting grid of mean gravity anomalies, and hence the geoid. The gravity anomaly types investigated comprise simple Bougner anomalies and refined Bougner anomalies, both computed using a constant topographic mass density. Irrespective of which anomaly type is used for gridding, the relevant additional correction terms are applied to yield an approximation of the mean Helmert anomaly. Regional gravimetric geoid models are then computed over Austalia and compared with one another and with GPS-levelling points on the Australian Height Datum. This shows that the application of terrain corrections before and after gravity gridding has only a relatively small effect on the computed goid in Australia.